Correction: Kovács et al. ABT-333 (Dasabuvir) Increases Action Potential Duration and Provokes Early Afterdepolarizations in Canine Left Ventricular Cells via Inhibition of IKr. Pharmaceuticals 2023, 16, 488 - Zsigmond Máté Kovács; József Óvári; Csaba Dienes; János Magyar; Tamás Bányász; Péter P. Nánási; Balázs Horváth; Adam Feher; Zoltan Varga; Norbert Szentandrássy (Pharmaceuticals)
Text Correction [...]